The effect of saffron serum on collagen density, inflammatory gene expression, and autophagy in UVB-exposed Wistar rats - Octavia, Chitra; Gunadi, Julia Windi; Adhika, Oeij Anindita; Ishak, Lani; Jasaputra, Diana Krisanti; Rosali, Alexandrina Everdine; Sanjaya, Ardo (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundSkin aging is a complex biological phenomenon influenced by intrinsic and extrinsic factors. Photoaging can be prevented by applying phytochemicals that have sun-protective properties. This study aimed to evaluate the effect of saffron serum to restore collagen density and autophagy processes and reduce inflammatory gene expression in UVB-exposed Wistar rats. MethodsAn experimental laboratory study was conducted involving 20 male Wistar rats that were divided into 4 groups: control, UVB, UVB + base serum, UVB + saffron serum exposed to UVB radiation for 5 weeks with a total dose of 3100 mJ/cm2. The skin was extracted then underwent Masson Trichrome staining and real-time PCR to obtain collagen density and gene expression. ResultsThe gene expression of MMP1, IL6, TNFá, LC3, and p62 was significantly increased in the UVB group compared to the control group. Topical administration of saffron serum significantly increased collagen density (p=0.001). Induction by UVB significantly increased LC3 (p=0.020) and p62 (p=0.030) gene expression, indicating an inhibition of autophagy. The saffron serum might modulate autophagy by increasing LC3, but not significant (p=0.495) and significantly decreasing p62 gene expression (p=0.001). As for MMP1, IL6, and TNFá, no significant decrease in gene expression was found in the UVB + saffron serum group compared to the UVB group. ConclusionSaffron serum increases collagen density and modulates autophagy in the skin of UVB-exposed Wistar rats. Inflammatory markers were increased after UVB induction, but no differences were found after saffron serum topical administration.